METODE PEMBELAJARAN BAHASA INDONESIA YANG INOVATIF TINGKAT SEKOLAH DASAR DENGAN TEORI BELAJAR SIBERNETIKA - Setiawan, Ricky; Muhimmah, Hitta Alfi; Subrata, Heru; Istiq'faroh, Nurul; Abidin, Zaenal; Noerdiana, Azizah Firdha (Universitas Negeri Surabaya, 2023)
The purpose of writing this article is to fulfill the assignment of the learning theory course, besides that, it can also find out the method of learning Indonesian by using learning media combined with learning methods based on the learning curriculum in accordance with the innovative government based on cybernetika learning theory. some studies of events that occur in learning in the present. Efficient learning methods do not only use one method and the learning methods applied in the classroom must be in accordance with the material as well as the innovative teacher will produce student learning outcomes that are creative, productive, and well informed and correct. According to Anggit Sri, et al (2013), the learning process is a process of student interaction with learning resources in a learning environment. Learning is assistance provided by educators so that the process of acquiring knowledge and knowledge, mastering skills, and behavior, as well as forming attitudes and beliefs in students occurs. In other words, learning is a process to help learners to learn well. This innovative learning is equipped with very varied models with syntax or steps. These include direct learning, cooperative learning, problem-based learning, inquiry, or learning through discovery. Thus this paper is made with the hope that it can be one of the references for every reader in developing his ability to develop a learning process based on the principles of innovative learning.